Anthropogenic particle dispersions in topsoils of the Middle Nile Delta: a preliminary study on the contamination around industrial and commercial areas in Egypt - Abu Khatita, Atef M.; de Wall, Helga; Koch, Roman (Environmental Earth Sciences, 2016)
Keywords: Anthropogenic particles; Magnetic spherules; Magnetic susceptibility; Nile Delta; Urban dust

Barkerina dobrogiaca Neagu, 2000, a Valanginian marker taxon from the northern Neotethysian margin - Schlagintweit, Felix; Bucur, Ioan I.; Granier, Bruno; Koch, Roman (Cretaceous Research, 2019)
Barkerina dobrogiaca Neagu (Valanginian of Romania), a medium-sized complex benthic foraminifera, is described from the Valanginian of the Pontides, NE Turkey. Barkerina dobrogiaca differs from the type-species B. barkerensis Frizzell & Schwartz (Albian of Texas) by its small size, and comparably thin septula and test wall. The present paper is a further contribution to the knowledge of inventory and faunal assemblages of Valanginian shallow-water carbonates. Compared to the classical Urgonian (Hauterivian to lower Aptian) these are still incompletely known. Together with another form reported from the Barremian of Romania, it also shows that representatives of Barkerina Frizzell & Schwartz are well present in the Neotethysian realm.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Biostratigraphy; Early Cretaceous; Exoskeleton; Foraminiferida; Paleobiogeography; Systematics

Die moderne Computer-Tomographie (Modell v|tome|x s 240 von GE/Phoenix) am Lehrstuhl für Paläoumwelt (GZN, Erlangen) – Methodik und Anwendungsbeispiele - Schulbert, Christian; Koch, Roman (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2017)
Keywords: Mikro-Computer-Tomographie

Matera building stones: Chemical, mineralogical and petrophysical characterization of the calcarenite di gravina formation - Bonomo, A. E.; Lezzerini, M.; Prosser, G.; Munnecke, Axel; Koch, Roman; Rizzo, G. (2019 IMEKO TC4 International Conference on Metrology for Archaeology and Cultural Heritage, MetroArchaeo 2019, 2019)
Matera (Basilicata, southern Italy) was awarded the World Heritage Site status by the UNESCO since 1993, and has been named the European Capital of Culture in 2019. It is one of the most ancient towns in the world, whose historical centre was totally built by a weakly lithified and highly porous lower Pleistocene sedimentary building stone, known as Gravina Calcarenite. This easily workable rock was quarried since prehistoric times, and it was used for building different kinds of constructions from the rupestrian settlement to gorgeous historic palaces during the XVIII century. Calcarenite, however, can be an extremely heterogeneous building material depending on the composition of the particles and their characteristics. After a geological survey, it was possible to recognize two main varieties of this building stone, which were in turn subdivided into six lithofacies (corresponding to sub-typologies of building stones). As a first approach, we have characterized, in terms of building stone quality, six lithofacies: basal bioclastic calcarenite, calcirudite-microconglomerate lithofacies, lithoclastic calcarenite, large bivalve bioclastic calcarenite, rhodolith bioclastic calcarenite, and fine bioclastic calcarenite. We focused on the three typologies that were mainly used as building stone (lithoclastic calcarenite, large bivalve bioclastic calcarenite, and fine bioclastic calcarenite). Mineralogical, petrographical and petrophysical analyses have been carried out according to European standard rules to highlight the main characteristics of the different calcarenite types when used as building stones. These three lithofacies show different petrophysical behavior indicating that large bivalve calcarenite and lithoclastic calcarenite lithofacies have slightly different but characteristic mechanical properties related to the primary influence of grain composition, early cementation and micrite contents. Moreover, fine bioclastic calcarenite lithofacies results to be the worst building stone because it is intensely heterogeneous in porosity, cementation and general petrophysical features because of its intense bioturbation.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Building stone; Cultural heritage; Petrographic characterization; Petrophysical properties

Matera building stones: Comparison between bioclastic and lithoclastic calcarenites - Bonomo, Agnese Emanuela; Lezzerini, Marco; Prosser, Giacomo; Munnecke, Axel; Koch, Roman; Rizzo, Giovanna (Building Materials, Materials Design and Applications, 2019)
Matera (Basilicata, southern Italy) was awarded World Heritage Site status by the UNESCO since 1993, and it will be the European Capital of Culture in 2019. It is one of the most ancient towns in the world, whose historical centre was totally built by only a moderately lithified and highly porous sedimentary building stone, known as Gravina Calcarenite. This easily workable rock was quarried since prehistoric times, and it was used for building different kind of constructions from the rupestrian settlement to the gorgeous historic palace during the XVIII century. Calcarenite, however, can be an extremely heterogeneous building material depending on the composition of the particles and their characteristics. After a geological survey, it was possible to recognize two main varieties of this building stone, which were in turn subdivided into six sub-typologies. As a first approach, we have characterized, in terms of building stone quality, the two main varieties: the bioclastic calcarenite and the lithoclastic calcarenite, sampled in the quarrying area to the North of Matera. The bioclastic calcarenite is from a new quarry in the upper part of the Calcarenite Formation, while the lithoclastic calcarenite is from an old quarry, inactive since 1965, in the lower part of the same formation. Mineralogical, petrographic and petrophysical tests have been carried out according to European Standards rules to highlight the main characteristics of different calcarenite types when used as building stone. Despite of their compositional differences, the bioclastic and lithoclastic calcarenite are both pure limestones with slightly different amounts of non-carbonates (silt quartz, clay minerals). The slightly different but characteristic mechanical properties clearly characterize the primary influence of grain composition, early cementation and micrite contents.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Building stone; Italian Unesco site; Petrographic characterization; Physical and mechanical properties

Matera’s Old Quarries: Geological and Historical Archives That Need Protection and Valorization - Bonomo, A. E.; Acito, A. M.; Prosser, G.; Rizzo, G.; Munnecke, Axel; Koch, Roman; Bentivenga, M. (Geoheritage, 2019)
The Sassi of Matera, UNESCO site since 1993, represents a human settlement completely integrated in the natural landscape. There, the development of the community is closely connected to the geology since prehistoric times. The Calcarenite di Gravina, a Pleistocene poorly lithified limestone onlapping a large area of the Apulian foreland in southern Italy, is the building stone that people used to carve their houses inside, and build the town outside. The use of calcarenite for housing began in the prehistory with the first human settlement, deepening natural caves which served as dwellings, while the mining activity began in the third century B.C., increasing until the nineteenth century in connection with the urban development of Matera. The calcarenite was carved out on site and used to build houses. In the eighteenth century, the great urban development of the city gave way to large mining activities in the northern area of Matera. Geomorphological analysis through aerial photographs and a geological survey in this area have been carried out to investigate the historical quarrying activities. In the present study, six quarry areas along the Appia Antica road are valuated: the Madonna delle Vergini topographic high; Cava della Palomba; Parco Scultura–Cava Paradiso; Cava del Sole, the Monumental Quarry Remains; Via Ridola inside the Piano, the highest area of Sassi. They represent peculiar and important examples to be safeguarded and valued. Their geomorphological, geostratigraphical and palaeontological elements provide useful information for understanding the territory evolution in the last two millennia.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Geo-valorization; Geological itinerary; Mining activities; Reused quarries; Soft limestone

Sources identification and contamination assessment of heavy metals in soil of Middle Nile Delta, Egypt - Abu Khatita, Atef M.; Koch, Roman; Bamousa, Abdullah O. (Journal of Taibah University for Science, 2020)
Sedimentological and geochemical studies are integrated to determine the potential of heavy metals in the Middle Nile Delta soil. Four sources of trace elements were identified; a geogenic source includes Fe, Co, Cr, Ni and V, along with Ca that partly enhanced by anthropogenic input, and three dissimilar anthropogenic sources grouped the elements as follow; As, Pb, Zn Cu, Ba and P which derived mainly from industrial activities; Ba, Pb, Zn and Cu group is likely dispersed by traffic emissions, and P, As and Cu elements group which influenced by agrochemical application and drain water irrigation. The concentrations of studied elements increasing with decreasing the particle size. Moreover, two groups of mineral assemblages of soil are recognized; the first group deposited with one particle fraction and inherited from parent materials, The second one includes non-silicate minerals clasts, deposited with more than one fraction and most likely of anthropogenic source.
CRIS-Team WoS Importer:2020-06-23

Spumispongia merklei nov. sp. (Porifera) from the Upper Jurassic (South Germany, Swabian Alb, Blautal) - Senowbari-Daryan, Baba; Koch, Roman (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2012)
UnivIS-Import:2017-11-07:Pub.2012.nat.dgeo.IGM.LP.spumis

Über das Alter und Altern von Gesteinen - Koch, Roman; Stollhofen, Harald (Geologische Blätter für Nordost-Bayern und angrenzende Gebiete, 2009)
UnivIS-Import:2015-04-14:Pub.2009.nat.dgeo.IGM.LG.berdas